ANCIENT METHODS OF SKIN INTERVENTION – ACUPUNCTURE PREDECESSORS? - Nikolay Dimitrov; Nikola Tomov; Ivelina Ivanova; Stilyan Iliev; Dimitrinka Atanasova; Dimitar Sivrev (Science & Research)

(untitled)
It has been proposed, that the very first therapeutic methods involved applying pressure or needling painful spots on the body surface. Ancient antropomorphic figurines and drawings, showing markings on the body, have been found. Those markings could be interpreted as special points, body painting, piercings, scarification, tattoos, or needling spots. In the present study we discuss the possibility that such historical therapeutic methods have given rise to the acupuncture. We study possible methods of skin intervention, we compare ancient tools and juxtapose the spots, in which modern acupuncture intervenes – the biologically active points (BAP). During acupuncture, needles of various materials (stone, bone, wood or metal) are temporarily inserted in specific points of the body. Body piercing and tattooing are contemporary used ancient methods, spread all over the world. We presume, that they could have been used not only ritualistically, but also as a therapeutic modality. Ancient mummies show tattoos in the form of lines, dots, or circles, often placed in BAP. Furthermore, it could be assumed, that they were therapeutically applied, since the tattooed individuals suffered from ailments, coinciding with the placement of tattoos in an attempt of treatment. Many historically used instruments that could be used in body piercing and tattooing, resemble the contemporary tools of acupuncture, points of application of tattoos and needles are also closely associated. In the present paper we presume, that different healing methods could have existed simultaneously for a long time. We also discuss the probability of acupuncture being a derivative of ancient methods of superficial skin intervention, such as tattooing and body piercing.